Critical Discourse Analysis Of Education Issues On The Kick Andy Show - Putri Erwina Pratiwi; Marlina A. Tambunan; Junifer Siregar (STABN RADEN WIJAYA WONOGIRI, 2025)
This study aims to determine a Critical Discourse Analysis of Educational Issues on the Kick Andy Program . This study uses a qualitative approach because it aims to understand the meaning behind the text, language, and discourse displayed in media broadcasts, especially the Kick Andy program. 1. Topic Bullying Among Young People. This broadcast emphasizes that bullying is still a serious problem among teenagers. Bullying victims not only experience physical injuries, but also long-term psychological trauma. The root of the problem of bullying often arises from the social environment, low self-control, lack of empathy, and the weak role of families and schools in prevention. 2. CSR Theme in the Field of Inclusive Education. This broadcast shows that inclusive education supported by CSR (Corporate Social Responsibility) programs is able to open wider access for children from various backgrounds, including those with disabilities. Inclusive education emphasizes equal opportunities and respect for diversity as a foundation for building a more just and tolerant generation. 3. Theme Bullying at Bunda Mulia University. The bullying case raised highlights that this problem does not only occur at the elementary and secondary school levels, but can also continue in universities. An academic environment that should support self-development can instead become a place of discrimination, intimidation, and social pressure if not managed properly. This demonstrates the need for adequate regulation, oversight, and counseling services at universities. 4. Theme: Flying High to Achieve Dreams. This program provides inspiration that limitations are not a barrier to achieving goals. The stories of the speakers prove that with hard work, an unyielding spirit, and community support, someone can realize their dreams despite facing various obstacles.